IMPLEMENTATION OF THE WORDWALL PLATFORM IN ELEMENTARY SCHOOL LEARNING TO OVERCOME STUDENT BOREDOM DURING LEARNING - Sutrisno; Nashrullah; Redna (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to evaluate the effectiveness of implementing the Wordwall platform in overcoming student boredom during learning at SDN 8 Mamboro. Wordwall is a web-based application that allows teachers to create interactive quizzes, educational games, and engaging assessment tools. This research uses an experimental pre-test post-test method with a control group, where one class group uses Wordwall as an interactive learning medium, while the control group uses conventional learning methods. This research was conducted in three cycles which included initial implementation stages, strategy adjustments, and optimization of Wordwall use. Data was collected through initial tests (pre-test), direct observation, final tests (post-test), and questionnaires to evaluate student experiences. The results showed that implementing Wordwall significantly increased student engagement and motivation. In the first cycle, students showed increased enthusiasm and participation in class. Adjustments in the second cycle included increasing the variety of educational games and technical training, which more evenly increased student engagement. The third cycle focused on optimizing Wordwall use and comprehensive evaluation, showing improvements in students' understanding of the material and academic achievement. The conclusion of this research is that Wordwall is effective in overcoming student boredom and improving the quality of learning at SDN 8 Mamboro. Recommendations for further development include the continued integration of technology in learning to create a dynamic and engaging learning environment.